Safe laparoscopic cholecystectomy: A systematic review of bile duct injury prevention - van de Graaf, Floyd W.; Zaïmi, Ina; Stassen, Laurents P.S.; Lange, Johan F. (International journal of surgery (London, England), 2018)
Since the introduction of laparoscopic cholecystectomy (LC), a substantial increase in bile duct injury (BDI) incidence was noted. Multiple methods to prevent this complication have been developed and investigated. The most suitable method however is subject to debate. In this systematic review, the different modalities to aid in the safe performance of LC and prevent BDI are delineated. A systematic search for articles describing methods for the prevention of BDI in LC was conducted using EMBASE, Medline, Web of science, Cochrane CENTRAL and Google scholar databases from inception to 11 June 2018. 90 studies were included in this systematic review. Overall, BDI preventive techniques can be categorized as dedicated surgical approaches (Critical View of Safety (CVS), fundus first, partial laparoscopic cholecystectomy), supporting imaging techniques (intraoperative radiologic cholangiography, intraoperative ultrasonography, fluorescence imaging) and others. Dedicated surgical approaches demonstrate promising results, yet limited research is provided. Intraoperative radiologic cholangiography and ultrasonography demonstrate beneficial effects in BDI prevention, however the available evidence is low. Fluorescence imaging is in its infancy, yet this technique is demonstrated to be feasible and larger trials are in preparation. Given the low sample sizes and suboptimal study designs of the studies available, it is not possible to recommend a preferred method to prevent BDI. Surgeons should primarily focus on proper dissection techniques, of which CVS is most suitable. Additionally, recognition of hazardous circumstances and knowledge of alternative techniques is critical to complete surgery with minimal risk of injury to the patient. •Several methods to prevent bile duct injury demonstrate beneficial effects.•Articles covering the Critical View of Safety technique report the lowest incidence.•Evidence to either support or abandon intraoperative cholangiography is scarce.•Fluorescence imaging is a promising technique, however is still in its infancy.•A preferred method cannot be recommended due to the low quality of studies available.